On the solution of the convolution equation with a sum-difference kernel - Ani G Barseghyan (Vestnik Samarskogo gosudarstvennogo tehničeskogo universiteta. Seriâ Fiziko-matematičeskie nauki, 2015)
The paper deals with the integral equations of the second kind with a sumdifference kernel. These equations describe a series of physical processes in a medium with a reﬂective boundary. It has noted some difficulties at applying the methods of harmonic analysis, mechanical quadrature, and other approaches to approximate solution of such equations. The kernel average method is developed for numerical-analytical solution of considered equation in non singular case. The kernel average method has some similarity with known strip method. It was applied for solution of Wiener-Hopf integral equation in earlier work of the author. The kernel average method reduces the initial equation to the linear algebraic system with Toeplitz-plus-Hankel matrix. An estimate for accuracy is obtained in the various functional spaces. In the case of large dimension of the obtained algebraic system the known methods of linear algebra are not efficient. The proposed method for solving this system essentially uses convolution structure of the system. It combines the method of non-linear factorization equations and discrete analogue of the special factorization method developed earlier by the author to the integral equations.